Fluid‐Dynamics‐Processed Highly Stretchable, Conductive, and Printable Graphene Inks for Real‐Time Monitoring Sweat during Stretching Exercise. (14th March 2021) - Park, Hong Jun; Jeong, Jae‐Min; Son, Seon Gyu; Kim, Seo Jin; Lee, Minkyung; Kim, Hyo Jeong; Jeong, Jihun; Hwang, Sung Yeon; Park, Jeyoung; Eom, Youngho; Choi, Bong Gill
Abstract: With the development of wearable electronics, the use of engineered functional inks with printing technologies has attracted attention owing to its potential for applications in low‐cost, high‐throughput, and high‐performance devices. However, the improvement in conductivity and stretchability in the mass production of inks is still a challenge for practical use in wearable applications. Herein, a scalable and efficient fluid dynamics process that produces highly stretchable, conductive, and printable inks containing a high concentration of graphene is reported. The resulting inks, in which the uniform incorporation of exfoliated graphene flakes into a viscoelastic thermoplastic polyurethane is employed, facilitated the screen‐printing process, resulting in high conductivity and excellent electromechanical stability. The electrochemical analysis of a stretchable sodium ion sensor based on a serpentine‐structured pattern results in excellent electrochemical sensing performance even under strong fatigue tests performed by repeated stretching (300% strain) and release cycles. To demonstrate the practical use of the proposed stretchable conductor, on‐body tests are carried out in real‐time to monitor the sweat produced by a volunteer during simultaneous physical stretching and stationary cycling. These functional graphene inks have attractive performance and offer exciting potential for a wide range of flexible and wearable electronic applications. Abstract : Highly stretchable, conductive, and printable graphene inks are fabricated using a fluid dynamics process, resulting in excellent electrochemical sensing performance of a potentiometric ion sensor even under a high level of a strain of 300%. Using a stretchable sensor on‐body tests are demonstrated in real‐time to monitor the sweat produced by a volunteer during simultaneous physical stretching and stationary cycling.